Private Health Insurance in Australia A Case Study - Colombo, Francesca (OECD Publishing, 2003)
Despite universal public insurance coverage, private health insurance (PHI) covers almost half of the Australian population - a high coverage rate in comparison with most other OECD countries. Reflecting the belief that a well-functioning health care system should be based on a mixed system of insurance and provision, Australia's policy makers have encouraged the development of private financing and delivery arrangements operating in parallel to the public system. PHI is seen as a vehicle for enhancing individuals' choice of provider and care options, and for reducing cost and demand pressures on public hospitals. Policy makers have intervened substantially in the private health insurance market. Regulation has promoted risk-pooling and incentive policies have stimulated the purchase of private cover. This paper analyses the Australian private health insurance market. It describes how PHI interacts with the public system, and assesses its contribution to equity, efficiency and ...
Keywords: Social Issues/Migration/Health; Australia